Resisting the molecular evolution of fitness: an investigation into the role of ploidy in the perturbed adaptability observed in an HTZ1 knockout - Reid, Jessica Laura (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.